Pedagogical Possibilities for Teaching Students to Play Musical Instruments in Music Clubs (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article reveals the content of extracurricular educational and educational work, the development of students' aesthetic thinking through instrumental performance in music circles, the content of meaningful spending of students' free time and pedagogical organization of their work on the basis of various activities. At the same time, the forms and methods of aesthetic education of students through music circle classes are highlighted.